Effect of regular swimming exercise to duration-intensity on neurocognitive function in cerebral infarction rat model. (2nd January 2019) - Song, Min-Keun; Kim, Eun-Jong; Kim, Jung-Kook; Park, Hyeng-Kyu; Lee, Sam-Gyu
ABSTRACT: Objective : This study investigated the effect of regular swimming exercise according to the duration-intensity on neurocognitive function in a cerebral infarction rat model. Methods : Forty male Sprague–Dawley 10-week-old rats, weighing 300 ± 50 g, were subjected to photothrombotic cerebral infarction. The remaining 36 rats were randomly divided into four groups ( n  = 9 per group: non-exercise (group A); swimming exercise of short duration-intensity (5 min/day, group B); swimming exercise of moderate duration-intensity (10 min/day, group C); and swimming exercise of long duration-intensity (20 min/day, group D). Exercise was performed five times a week for 4 weeks, beginning the day after cerebral infarction. Neurocognitive function was evaluated with the Morris water maze test. Immunohistochemistry and western blot analysis examined brain-derived neurotrophic factor (BDNF) and vascular endothelial growth factor (VEGF) at 4 weeks postinfarction. Results : At 4 weeks postinfarction, escape latency was found to be shorter in group C than in any of groups A, B, or D. Immunohistochemistry revealed the most significant immunoreactivity for BDNF and VEGF in group C. Western blot analysis demonstrated that BDNF and VEGF proteins were markedly expressed in group C. Conclusions : Regular swimming exercise of moderate duration-intensity may be the most effective exercise protocol for the recovery of neurocognitive function in cerebral infarction rat model.